Towards the geometric structure of small supported Au9 clusters on Si - D. Chekrygina (Nature Portfolio, 2018)
Abstract Ultra-small clusters containing few atoms are of high interest in both fundamental research and applications due to their specific functional, magnetic or chemical properties which depend on size and composition. The experimental results of the morphology of the size-selected clusters, consisting of few atoms can be an ideal benchmark for sophisticated theoretical models. With this motivation we have investigated the geometrical structure of mass-selected Au9 clusters deposited on a silicon substrate prepared by soft-landing conditions. We present results obtained experimentally by Grazing-Incidence Small-Angle X-ray Scattering (GISAXS). Considering the ultra-small size of the clusters and small quantities of material on the surface, we combined advanced techniques which allowed us to investigate the surface structure of the sample. The resulting structural sizes are in concordance with cluster theory. Using a model-based approach, the advanced X-ray techniques allow for understanding how to resolve the possible cluster structure, identify optimal experimental conditions and obtain the probable morphological information which is challenging to be obtained otherwise.